Etnopedagogi Pemanfaatan Tanaman Obat dan Pangan Baduy sebagai Sumber Belajar Kontekstual Literasi Biodiversitas di Sekolah Dasar untuk Mendukung Pencapaian SDGs - Nuraeni, Hasna; Suratno, Tatang; Fatihaturosyidah, Fatihaturosyidah; Rahmawati, Suci; Pramudya, Muhamad Daffa; Marsya, Khaira (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The local knowledge of the Outer Baduy community in Leuwidamar District, Lebak Regency, Banten, regarding the use of medicinal and food plants faces conservation challenges amidst social change and the decline in the inheritance of ecological values ????between generations. This study aims to identify the diversity of medicinal and food plants utilized by the Baduy community and analyze their potential as ethnopedagogical learning resources in elementary schools to support the achievement of Sustainable Development Goals (SDGs). This study uses a descriptive qualitative approach through field observations, in-depth interviews with traditional leaders and key informants, and documentation of taxonomically verified specimens. The results of the study found 52 plant species from 31 families, with a dominance of Zingiberaceae and Asteraceae, most of which function as medicinal plants. From the 52 species, 12 priority species were generated which were recommended for the development of contextual learning in elementary schools based on pedagogical criteria. In addition, ethnopedagogical practices of Baduy community biodiversity conservation were obtained in the form of pikukuh karuhun, such as the prohibition of cutting down forests, the use of natural fertilizers, and storing harvests in leuit, as well as the seven pillars of nature management. These results confirm that the ethnobotanical knowledge of the Baduy community has high pedagogical value and great potential to be used as a learning resource and integrated into contextual science learning to strengthen biodiversity literacy and ecological character of elementary school students, as well as support the achievement of SDG 4 (Quality Education) and SDG 15 (Terrestrial Ecosystems).